2012
DOI: 10.1007/s11033-012-1931-2
|View full text |Cite
|
Sign up to set email alerts
|

Study of NAT2 genetic polymorphism in West African subjects: example of an healthy non-smoker Senegalese population

Abstract: The NAT2 genetic polymorphism determines the individual acetylator status and, consequently, the capacity to metabolize, or not, drugs and xenobiotics which are substrates of NAT2. As the nature and frequency of the NAT2 polymorphisms vary remarkably between populations of different ethnic origins, genotyping strategies used to predict the acetylation phenotype need to be adapted for each particular population regarding their genetic backgrounds at this locus. As few data on the genetic polymorphism of NAT2 ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Actually, it has been reported that C282T and C481T SNPs are synonymous changes and seem to exert no effect on NAT2 acetylation capacity or protein stability (Zang et al, 2007;Selinski et al, 2013;Boukouvala, 2016). It has been shown that G191A, C345T, and A803G SNPs are missense mutations that cause amino acid changes in a mature protein (Walraven et al, 2008;Toure et al, 2012;Boukouvala, 2016). Polymorphisms C345T and A803G seem to have no functional effect on NAT2 enzyme, in contrast to the G191A SNP which has been associated with reduced catalytic activity (Toure et al, 2012;Selinski et al, 2013;Boukouvala, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actually, it has been reported that C282T and C481T SNPs are synonymous changes and seem to exert no effect on NAT2 acetylation capacity or protein stability (Zang et al, 2007;Selinski et al, 2013;Boukouvala, 2016). It has been shown that G191A, C345T, and A803G SNPs are missense mutations that cause amino acid changes in a mature protein (Walraven et al, 2008;Toure et al, 2012;Boukouvala, 2016). Polymorphisms C345T and A803G seem to have no functional effect on NAT2 enzyme, in contrast to the G191A SNP which has been associated with reduced catalytic activity (Toure et al, 2012;Selinski et al, 2013;Boukouvala, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that G191A, C345T, and A803G SNPs are missense mutations that cause amino acid changes in a mature protein (Walraven et al, 2008;Toure et al, 2012;Boukouvala, 2016). Polymorphisms C345T and A803G seem to have no functional effect on NAT2 enzyme, in contrast to the G191A SNP which has been associated with reduced catalytic activity (Toure et al, 2012;Selinski et al, 2013;Boukouvala, 2016). NAT2 G191A SNP variant presents equal allelic and genotypic distributions between the controls and pa- Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of nine SNPs were genotyped: rs2256871 in CYP2C9*9 and rs7900194 in CYP2C9*8 ; rs1057126 and rs15561 in NAT1 ; rs1041983, rs1801280, rs1799929, rs1799930 and rs1208 in NAT2 . …”
Section: Methodsmentioning
confidence: 99%
“…Quantitative PCR with TaqMan probes was used for CYP2C9 genotyping and Big Dye sequencing PCR for NAT1 and NAT2. For NAT1, the technique used is that described by Hsieh et al [35]; and for NAT2 as described by Touré et al [34].…”
Section: Methodsmentioning
confidence: 99%